Effect of platelet‐rich plasma on peri‐implant trabecular bone volume and architecture: A preclinical micro‐CT study in beagle dogs. Issue 12 (20th September 2019) - Huang, Yan; Li, Zhaokai; Van Dessel, Jeroen; Salmon, Benjamin; Huang, Bo; Lambrichts, Ivo; Politis, Constantinus; Jacobs, Reinhilde
Abstract: Objectives: To evaluate the peri‐implant trabecular bone volume and architecture changes with 6‐month follow‐up after local application of platelet‐rich plasma (PRP) and platelet‐poor plasma (PPP) using high‐resolution micro‐CT. Material and methods: Seventy‐two dental implants were placed into healed mandibular sites of 9 beagle dogs. Implants were randomly divided into 4 groups following a split‐mouth design: control I; control II; PPP; and PRP. Primary and secondary stabilities were assessed using resonance frequency analyses. At 1, 3, and 6 months after implant loading, trabecular structural parameters were evaluated at 0.5, 1, and 1.5 mm away from implants using micro‐CT (voxel = 20 μm). Results: Primary and secondary stabilities were equivalent in all conditions. PPP and PRP groups showed higher bone volume fraction (BV/TV) and trabecular thickness (Tb.Th) but lower trabecular separation (Tb.Sp) and total porosity percentage (Po (tot)) at all 3 time points. A significant decrease in BV/TV and Tb.Th was found for the control groups after 3 months of healing, while this was not observed in both the PPP and PRP groups. However, no distinct difference was found between the PRP and PPP groups over time. Moreover, as the investigated distance from the implant surface increased, BV/TV and Po (tot) within the same group and time point stayed the same, yet Tb.Th and Tb.Sp continued to increase. Conclusions: Platelet‐rich plasma and PPP with conventional implant placement lead to similar primary and secondary implant stability, but improved peri‐implant bone volume and structural integration. The present research does not seem to suggest a different bone remodeling pattern when using PRP or PPP.